Nunavik Inuit and Raglan Mine: New approaches to closure planning (isulinnisanganut parnasimautiit) - Arn Keeling (Journal of Political Ecology, 2025)
This article explores an experimental approach to mine closure planning and community participation that foregrounds the dialogue between technical and legal approaches to the mine and the knowledge and values of affected Indigenous communities. Located in the Inuit territory of Nunavik in the Canadian province of Québec, the Raglan Mine is the site of a unique collaborative approach to mine closure planning. Although the Raglan Mine is expected to remain operational for at least another 20 years, the Closure Plan Subcommittee was launched in March 2018 to establish and maintain a dialogue with the mine's Inuit partners about mine closure. The objective is "to integrate the traditional knowledge of the communities, but also to exchange the scientific knowledge of the technical experts and the mine." Drafted in collaboration with members of the Subcommittee, this article reviews the regulatory context for mine closure planning in Nunavik, including the lack of requirements for community-engaged planning or integration of socio-economic objectives. It also reviews the key milestones of the Subcommittee's work to date and assesses progress towards its objective of establishing culturally relevant closure goals and criteria, and the integration of Inuit knowledge, enterprise, and industry know-how in the closure planning process.